The Effect of Fly Ash Composition on The Hydrophobic Absorption, and Strength Properties of Concrete - Asri Vauzia; - Ratnawulan (PILLAR OF PHYSICS, 2022)
The use of concrete in buildings that indicate direct contact with water such as concrete preparation and roof requires waterproof concrete. The air entering the concrete through the capillary tubes formed during the formation process can be reduced by reducing the diameter of the microcapillary. Fly Ash is an additive that has seeds that are smaller than cement. After the fly ash in the concrete mixture reacts with cement and water, the diameter of the microcapillary formed will be smaller. The purpose of this study is to determine the effects of variations in the composition of flying ash on the hydrophobic, absorption, and concrete strength. Variations in the composition of flying ash are 0%, 5%, 10%, 15%, and 20%. Based on the test, the percentage of absorption in concrete aged 7 reached an optimal value at 5% percentage of flying ash with a value of 0.363%, whereas in concrete aged 14 days optimal value is obtained at the percentage of flying ash 5% with a value of a 0.5%. The biggest contact angle for the variation of 0% flying ash at the age of 7 days is 128.79⁰ and the lowest value for the variation in flying 15% is 100.41⁰. The highest compressive strength value occurs in the percentage of flying ash at 0% is 30,945 in 7 days of concrete age, and the lowest concrete compressive strength value is the percentage of fly ash at 15%, namely 16.05 MPa for concrete age 14 days